PENGUKURAN LANDFILL GAS PADA LAPISAN KEDUA PILOT PLANT DRY CELL DI TPA BANGKLET, KABUPATEN BANGLI, PROPINSI BALI - Rahardjo, Petrus Nugroho (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2011)
The gases produced from Sanitary Landfill are to be monitored and collected so asÃ‚Â not to cause environmental pollution. TPA Bangklet in Bangli District, Bali Province iscurrently being reviewed and further developed to be pilot Sanitary Landfill in Indonesia.Ã‚Â A system of monitoring and capturing or collecting LFG (Landfill Gas) has been done toBangkletÃ¢â‚¬â„¢s Sanitary Landfill of the dry Cell Pilot Plant, especially for the second layer.Ã‚Â LFG measurement results show the average value of 32.99% for CH4, 31.87% for CO2,Ã‚Â 5.4% for O2 and up to 29.68% for other gases. But the arrests and the collection of LFGÃ‚Â system still needs improvement, because there are some leaks that led to the entry ofÃ‚Â oxygen into the system and vice versa the LFG is released into the atmosphere. It isÃ‚Â suggested that the pattern of capture, and utilization of LFG monitoring system have toÃ‚Â be applied to all Sanitary Landfills located in Indonesia.Ã‚Â